Problems of Transmission with Inhomogeneous Principal Conjugation Conditions and High-Accuracy Numerical Algorithms for Their Discretization - Deineka, V. S.; Sergienko, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We construct new problems of transmission and high-accuracy computational algorithms for their discretization.